Co jezuita wiedział o Boskich posłańcach? Motywy anielskie w piśmiennictwie Piotra Skargi - Dybek, Dariusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
Piotr Skarga is one of the most prominent Polish writers of the 16th century. Today he is mostly regarded as a polemicist, heavily engaged in political matters. However, during his lifetime, he was considered as a religious writer. Lives of the Saints held a significant importance among his work, as well as his sermons (especially appreciated by Catholics, since people of other faiths thought of Skarga as a sworn enemy). In these writings there are a lot of references to the angels (around 500 mentions), although it does not make him an angelologist. His remarks on the angels are in accordance with the Catholic doctrine and decrees of the Council of Trent. Skarga’s favorite motives were: hierarchical structure of existence (man should aim high, to the angels), angelic hierarchy (following Pseudo-Dionysius the Areopagite), the court of God (with a special role of the courtier angels), the angelic army (with God as its leader, interfering in history, also the history of Poland), singing of the angels (one of the most common themes, coming from the Biblical Apocrypha), the Guardian Angel (belonging to everyman, not only ardent Catholics) and the angelic cult (one of the determinant aspects of Christianity). Although Skarga was very vigilant not to write anything that would not be in accordance with the Catholic teachings, he was using religious motives to reflect upon the politics, for example he regarded divine monarchy as a model for earthly monarchy.